FAKTOR- FAKTOR PENDORONG PENGGUNAAN ISLAM MODERAT SEBAGAI IDENTITAS BARU POLITIK LUAR NEGERI INDONESIA TAHUN 2004-2014 - Andi Purwono (LP2M, 2016)
This research aims to answer the reasons why did Susilo Bambang Yudhoyono’s government in 2004-2014, using Islam as identity in Indonesia forein policy. Before this period, Islam had never been expressed in Indonesia foreign policy. Leader like Soekarno and Soeharto tried to keep Indonesia foreign policy from islamic influence. Using qualitative method and Albert Hourani theoritical analysis, this research found that there are three reasons of this. First, Islam has been used to justify SBY policy. Second, to mobilize domestic support, and three, to reach international support and Indonesia image. Keywords: foreign policy, Islam, identity, domestic support, international image